A study on the physicochemical properties of a graphite/polybenzoxazine composite for bipolar plate of polymer electrolyte membrane fuel cells - Kim, Seon Gi; Kim, Jeong-Heon; Yim, Jin-Heong (Macromolecular research, 2013)
The effects of graphite content, compression molding conditions, and types of catalysts on the mechanical and electrical properties and corrosion resistance of a graphite composite based on benzoxazine resin for the bipolar plate of polymer electrolyte membrane fuel cells (PEMFC) are provided in this study. Four kinds of catalysts based on imidazole (Im) acting as catalysts are investigated in order to enhance the physicochemical properties of the graphite/polybenzoxazine composites. The characteristics of the graphite composites based on benzoxazine resin with 85 wt% graphite content prepared via compression molding satisfy the US DOE targets for the bipolar plate of a PEMFC. A graphite composite based on polybenzoxazine with an Im-based catalyst having a relatively long alkyl chain shows the best performance in terms of flexural strength and corrosion resistance without sacrificing electrical conductivity. This graphite/polybenzoxazine composite can be successfully molded as a bipolar plate with excellent physicochemical properties through a compression molding process.